2016
DOI: 10.1002/ejoc.201600519
|View full text |Cite
|
Sign up to set email alerts
|

S‐Geranylated 2‐Thiouridines of Bacterial tRNAs: Chemical Synthesis and Physicochemical Properties

Abstract: Herein, we report the first synthesis of two recently discovered, prenylated 2‐thiouridine derivatives, 5‐methylaminomethyl‐S‐geranyl‐2‐thiouridine (mnm5geS2U) and 5‐carboxymethylaminomethyl‐S‐geranyl‐2‐thiouridine (cmnm5geS2U). S‐Geranylated 2‐thiouridines were obtained by S‐alkylation of the parent (c)mnm5S2U nucleosides suitably protected at their C5‐alkylamino function. Comparative physicochemical studies of S2U, mnm5S2U, and cmnm5S2U and their S‐geranylated derivatives revealed unique highly hydrophobic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…The reported unexpected higher mobility (shorter retention time in RP-HPLC) of the geranylated product compared to its native precursor (T instead of geS2T) was explained by the Authors as ‘a special structural alignment in the oligonucleotide’ (15). Our observations are in agreement with recently obtained log P data determined at the level of R5geS2U nucleosides (R = H, mnm or cmnm), which indicate a higher lipophilicity of these compounds compared to their parent R5S2Us (16). In the present studies, we measured the partition coefficients of the U, S and geS oligonucleotides in a water/1-octanol biphasic system.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The reported unexpected higher mobility (shorter retention time in RP-HPLC) of the geranylated product compared to its native precursor (T instead of geS2T) was explained by the Authors as ‘a special structural alignment in the oligonucleotide’ (15). Our observations are in agreement with recently obtained log P data determined at the level of R5geS2U nucleosides (R = H, mnm or cmnm), which indicate a higher lipophilicity of these compounds compared to their parent R5S2Us (16). In the present studies, we measured the partition coefficients of the U, S and geS oligonucleotides in a water/1-octanol biphasic system.…”
Section: Discussionsupporting
confidence: 92%
“…Escherichia coli, Enterobacter aerogenes, Pseudomonas aeruginosa and Salmonella Typhimurium ), detailed data on the properties and cellular functions of these tRNAs have not been reported, with the exception of data on the hydrophobicity and structural characteristics of mnm5geS2U and cmnm5geS2U at the nucleoside level (16). …”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that bands around 240 nm may be attributed to a conjugated C2=N3-C4=O4 π-bond system present in 4-pyrimidinone-like scaffolds, e.g., in S-geranylated-2-thiouridine (λ max ca. 240 nm) [76], 4-pyrimidinone riboside (λ max ca. 247 nm for mnm5H2U) [77], and 5-methyl-4-pyrimidinone 2 -deoxyriboside (λ max ca.…”
Section: Discussionmentioning
confidence: 99%
“…The excess selenium was filtered off and vacuum distillation (b.p. 51-52°C/0.1 mmHg) of the filtrate furnished O,O,O-tris(trimethylsilyl) phosphoroselenoate (1.67 g, 0.0044 mol), 63% yield; spectral data: 31…”
Section: Synthesis Of Selenophosphate Sepo 3 3àmentioning
confidence: 99%
“…2A) shows that the retention times (R T ) for U-RNA, S2U-RNA, and Se2U-RNA are very similar (ca. 28 min) while the geS2U-RNA elutes at significantly higher concentration of the organic phase (R T > 41 min) because of the presence of the hydrophobic geranyl group [21,31]. The MALDI-TOF MS analysis of the 1 : 1 mixture of S2U-RNA and Se2U-RNA shows the corresponding signals of virtually the same intensity (Fig.…”
Section: Synthesis and Characteristics Of Rna Modelsmentioning
confidence: 99%